2009
DOI: 10.1029/2009jd011955
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of horizontal in‐mixing into the lower tropical stratosphere

Abstract: [1] Based on the HALOE and SHADOZ observations of ozone (O 3 ) and on a simple conceptual model of transport and photochemistry, the seasonality of O 3 within the stratospheric part of the tropical tropopause layer (TTL) extending between 360 and 420 K potential temperature is discussed. We show that the seasonality of O 3 diagnosed on pressure (p) surfaces has a significantly larger annual cycle compared with the same kind of analysis on surfaces with constant potential temperature (q), in particular around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 40 publications
(64 reference statements)
9
92
2
Order By: Relevance
“…However, sensitivity calculations using 5 month instead of 3 month back trajectories give very similar results (not shown). This result supports the argument of Konopka et al (2009) and Konopka et al (2010) that the annual cycle in lower stratospheric ozone is a consequence of more inmixing of stratospherically old air during the boreal summer months.…”
Section: Reconstruction Of Tropical Mean and Local In-situ Observationssupporting
confidence: 80%
See 1 more Smart Citation
“…However, sensitivity calculations using 5 month instead of 3 month back trajectories give very similar results (not shown). This result supports the argument of Konopka et al (2009) and Konopka et al (2010) that the annual cycle in lower stratospheric ozone is a consequence of more inmixing of stratospherically old air during the boreal summer months.…”
Section: Reconstruction Of Tropical Mean and Local In-situ Observationssupporting
confidence: 80%
“…Avallone and Prather (1996) showed that in principle the same information can be obtained from the vertical gradient in tropical lower stratospheric ozone. Randel et al (2007) and Konopka et al (2009) further studied the relation between upwelling and ozone, and the possible role of horizontal, isentropic in-mixing. Our results using the full 4-dimensional transport as represented by trajectories suggest that diabatic dispersion may play a significant role for tropical lower stratospheric ozone concentrations.…”
Section: Mean Transport and Dispersion In The Ttl And Lower Stratospherementioning
confidence: 99%
“…One relevant difference between KP and the present work is the choice of the vertical coordinate. Konopka et al (2009) show that the amplitude of the seasonal cycle in ozone is reduced by more than 50 % when analyzed on isentropic levels. This is because of the strong correlation between temperature and ozone (see Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…6 and 7) have significant residuals, which are likely due to eddy transport not resolved in our analyses plus uncertainties in the resolved terms. The importance of eddy transport for ozone in the tropical lower stratosphere has been suggested by Konopka et al (2009Konopka et al ( , 2010 and Ploeger et al (2012), hereafter KP. The results of KP deserve further discussion.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example, the large ozone annual cycle has been attributed to the annual cycle in the tropical mean upwelling [Randel et al, 2007], and a negative trend deduced from Stratospheric Aerosol and Gas Experiment (SAGE) ozone data has been attributed to an increase in the upwelling bringing more ozone-poor air into the lower stratosphere [Randel and Thompson, 2011]. More recent studies have presented evidence that quasi-horizontal mixing with the extratropics plays an important role, at least for the annual cycle [e.g., Konopka et al, 2009Konopka et al, , 2010Ploeger et al, 2012;Abalos et al, 2012Abalos et al, , 2013aAbalos et al, , 2013b. While the above studies have all used ozone observations to estimate transport rates, they have all focused on variations in the tropic-wide average (of ozone and upwelling).…”
Section: Introductionmentioning
confidence: 99%